Service charges and implications on service delivery at the Elias Motsoaledi Local Municipality, South Africa - Mathebula, N. E.; Leopeng, K. G. (FMLIC - Conference Proceedings, 2024)
The aim of this paper is to assess the impact and the effect of non–payment of municipal services on service delivery in the Elias Motsoaledi Local Municipality, Limpopo Province in South Africa. Municipalities, given their proximity with the constituents, are responsible for delivering basic services such as water, electricity, road maintenance, refuse collection and sanitation amongst others to communities under their jurisdiction. Various pieces of legislation permit municipalities to charge for services rendered to communities particularly water and electricity. The paper adopted both qualitative and quantitative research approaches for data collection and analysis. Households in the selected villages (Motetema, Tambo and Groblersdal) within the Elias Motsoaledi Local Municipality were randomly selected to participate in the study together with the officials of the Municipality. Non-payment for municipal services is a great challenge in the South African local government and threatens the financial viability and sustainable service delivery. This paper probes the nature of non-payment of municipal services, its impact on service delivery and the methods used to tackle non-payments in order to make recommendations. The findings reveal that indeed revenue collection and non-payment of municipal service charges is a challenge in Elias Motsoaledi Local Municipality and therefore has dire impact on effective service delivery. This is due to unwillingness to pay for service charges, unemployment, poor quality services, low income amongst other challenges. Thus, the municipality is unable to generate adequate revenue to deliver better services.
Keywords: Revenue; Revenue collection; Non-payment; Service delivery; Local government